2013
DOI: 10.1016/j.yexcr.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Cell and tissue mechanics in cell migration

Abstract: Migrating cells generate traction forces to counteract the movement-resisting forces arising from cell-internal stresses and matrix adhesions. In the case of collective migration in a cell colony, or in the case of 3-dimensional migration through connective tissue, movement-resisting forces arise also from external stresses. Although the deformation of a stiffer cell or matrix causes larger movement-resisting forces, at the same time a larger stiffness can also promote cell migration due to a feedback between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(126 citation statements)
references
References 44 publications
7
115
0
Order By: Relevance
“…During cell migration, dynamics reorganization of cytoskeleton in specific sites drive the cell to contraction and/or rotation. Hence, relatively loose cytoskeleton is beneficial for cell migration, either through reducing cell stiffness to easily pass through small holes or through quick degradation and assembly of cytoskeleton to lead cells stretch to crawl forward (Friedl et al 2011;Lange and Fabry 2013). In this study, we found that SMG markedly inhibited BMSCs migration, accompanied with the augmented F-actin cytoskeleton formation and abnormal cell stiffness.…”
Section: Discussionmentioning
confidence: 56%
“…During cell migration, dynamics reorganization of cytoskeleton in specific sites drive the cell to contraction and/or rotation. Hence, relatively loose cytoskeleton is beneficial for cell migration, either through reducing cell stiffness to easily pass through small holes or through quick degradation and assembly of cytoskeleton to lead cells stretch to crawl forward (Friedl et al 2011;Lange and Fabry 2013). In this study, we found that SMG markedly inhibited BMSCs migration, accompanied with the augmented F-actin cytoskeleton formation and abnormal cell stiffness.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, cell migration, cell adhesion, and cell division have all been shown to depend on cell mechanics (1)(2)(3)(4)(5). Most studies have focused on the mechanical cross talk between the cell and its microenvironment at the whole-cell or the tissue level.…”
mentioning
confidence: 99%
“…collective cell migration | avalanches | universality | vascular endothelial cadherin | collagen substrate C ollective cell movement depends on intracellular biological mechanisms as well as environmental cues due to the extracellular matrix (1)(2)(3)(4)(5), mainly composed of collagen which is organized in hierarchical structures, such as fibrils and fibers. The mechanical properties of collagen fibril networks are essential to offer little resistance and high sensitivity to small deformations, allowing easy local remodeling and strong strain stiffening needed to ensure cell and tissue integrity (6).…”
mentioning
confidence: 99%